Effect of meta-Topolin on morphological, physiochemical, and molecular dynamics during in vitro regeneration of Salix tetrasperma Roxb. - Zubair Altaf Reshi; Fohad Mabood Husain; Mehrun Nisha Khanam; Saad Bin Javed (BMC Plant Biology)
Abstract An efficient in vitro propagation protocol has been established for a valuable medicinal plant, Salix tetrasperma using mature nodal explants. The investigation aimed to observe the influence of various combinations and concentrations of cytokinins (mT, BA, and Kn) and auxins (NAA, IAA, and IBA) on regeneration potential using the Murashige and Skoog (MS) medium. Among individual cytokinin treatments, 5.0 µM mT resulted highest response of 92% with maximum shoot number (11.6 ± 0.08) per explant and shoot length (4.5 ± 0.22 cm) after 12 weeks of culture. However, synergistic treatment of mT (5.0 µM) and NAA (0.5 µM) further improved proliferation with (21.3 ± 0.40) shoots per explant and (6.9 ± 0.13 cm) shoot length in 96% cultures after 12 weeks of incubation. Rooting from in vitro raised microshoots was achieved on ½ MS medium supplemented with various concentrations of low-dose auxins. The highest number of roots (10.4 ± 0.20) per shoot with mean root length (5.7 ± 0.11 cm) with maximum rooting frequency (97%) was observed in 0.5 µM IBA, after 4 weeks of culture. The rooted plantlets achieved a remarkable 86% survivability rate, when transferred to ex vitro conditions during acclimatization. Analysis of photosynthetic parameters and their characteristics during the acclimatization phase revealed a gradual decline in photosynthetic attributes during initial weeks; however, a significant improvement was noted as the growth proceeded. SEM analysis revealed the ultra-morphological structural differences between in vivo and in vitro derived leaves of S. tetrasperma. Moreover, DPPH assay observed differential antioxidant activity of in vitro raised plantlets throughout the acclimatization period. The GC-MS analysis from leaf extracts of donor plants and in vitro derived plantlets has revealed a broad spectrum of phytochemical compounds with significant pharmacological properties. No polymorphism in the banding pattern was found when the genetic fidelity of the regenerated plants was evaluated using SCoT primers, indicating the clonal stability of micropropagated plants. This study is the first to explore the use of mT in regeneration of S. tetrasperma, showing its more effectiveness than BA and Kn.